Establishment of landslide early-warning indicator using the combination of numerical simulations and case matching method in wushan open-pit mine - Zhang, Penghai; Deng, Wenxue; Liu, Feiyue; Wang, He; Dong, Xin; Niu, Peng (Frontiers in Earth Science, 2022)
Landslide seriously threatens the safety of human life and property. In order to warn the potential landslides, this paper firstly characterize rock mass physical and mechanical parameters based on the core RQD identification, geostatistics interpolation method and the Hoek-Brown criterion. Then, the rock mass physical and mechanical parameters characterization model was transformed to the slope numerical models, and the potential landslide characteristics were predicted combining with the monitoring data and numerical simulation. Finally, based on the matching between potential landslide and historical landslide cases, the early warning indicator of potential landslide is set as the posterior indicators of historical landslide with the highest similarity. The results show that the potential landslide mode of the west and southwest slope of Wushan open-pit mine is single step wedge landslide and integral incline landslide, respectively. They are the most similar to those in Anjialing open-pit Mine and Fushun West Open-pit Mine respectively. Based on the posterior warning indexes of the most similar landslide cases, the warning indicators of the west and southwest slope are set as 12.7mm/d and 135.2mm/d. The method proposal in this paper provides a reference for the establishment of slope early warning indicators in open-pit mine.